Response of chickpea varieties to boron application in calcareous and terrace soils of Bangladesh - Quddus, MA; Hossain, MA; Naser, HM; Naher, N; Khatun, F (Bangladesh Journal of Agricultural Research, 2018)
An experiment was conducted at Madaripur and Gazipur during rabi (winter) season of 2012-13 and 2013-14 to determine the optimum dose of B for different varieties of chickpea (Cicer arietinum L.). There were 12 treatment combinations comprising three varieties (BARI Chola-5, BARI Chola-8 and BARI Chola-9) and four levels of boron (0, 1, 1.5 and 2 kg ha-1) along with a blanket dose of N20P20K25S10Zn2 kg ha-1. Boron was applied as H3BO3. Results showed BARI Chola-9 with 1.5 kg B ha-1 produced the highest seed yield of 1338 kg ha- 1 at Madaripur and 2218 kg ha-1 at Gazipur. Nodulation, nitrogen (N) and protein contents were also found highest for the same variety and B treatment. The other two varieties (BARI Chola-5 and BARI Chola-8) also performed higher yield in the plot receiving 1.5 kg B ha-1 compared to 1 kg B ha-1 or 2 kg B ha-1 at both locations. The results suggest that BARI Chola-9 and 1.5 kg B ha-1 along with N20P20K25S10Zn2 kg ha-1 could be used for achieving higher yield of chickpea in calcareous and terrace soils of Bangladesh. Bangladesh J. Agril. Res. 43(4): 543-556, December 2018